THE ROLE OF THE FAMILY IN PROTECTING CHILDREN DURING THE PANDEMIC - Ida Musofiana; Andri Winjaya Laksana; Andi Aina Ilmih (LAW FACULTY UNISSULA, 2021)
This article is the result of community service on child protection during the pandemic. Children are the holders of the future of the country in the future life. Shared responsibility of the community and the state, including the government. The pandemic situation has hampered several activities in the aspects of education, economy, social, including law. The purpose of this community service in the context of responsibility and guarantee for the growth and development of children is a concern, during a pandemic children will continue to do their best in protecting basic rights to ensure good growth and development in the future. Methods of community service use participatory approach. The results of this community service are the effort to protect children during the Covid-19 pandemic is a regulation during this pandemic, the government issued Presidential Decree No. 12 of 2020 concerning the Determination of Non-Natural Disasters Spreading Covid-19 as a National Disaster. This was followed by the ratification of Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating Handling of Corona Virus Disease 2019.